Ecotourism/ by Kulwant Singh Pathania and Arun Kumar - Pathania, Kulwant Singh (New Delhi, 2008)
book wholeheartedly analyses the basic concepts and core elements of this complex phenomena otherwise known as ecotourism, in a simple language, making it extremely useful for tourists, research scholars and the teachers working in this field.
Keywords: Ecotourism